THE INFLUENCE OF MACROECONOMIC FACTORS, INVESTMENT RISK, AND FINANCIAL PERFORMANCE ON STOCK RETURN OF THE LQ45 INDEX 2016-2021 PERIOD AT THE IDX - Najihul Mujahidah; Hety Budiyanti; Nurman; Anwar Ramli; Muh. Ichwan Musa (Transpublika Publisher, 2023)
Macroeconomic factors refer to broader economic indicators such as inflation, interest rates, GDP growth, and exchange rates. These factors can significantly impact stock returns as they reflect the overall health and performance of the economy. This study aims to analyze the effect of macroeconomic factors, investment risk, and financial performance on stock returns for the LQ45 index for the 2016-2021 period. The research employs quantitative methods and multiple linear regression analysis to systematically explore the relationships between these variables. Data from 27 companies were sampled based on specific criteria, and the analysis was conducted using the SPSS version 22 program. The findings reveal that inflation has a significant and positive effect on stock returns for the LQ45 index, while interest rates have a non-significant negative impact. Additionally, Beta shows a positive but non-significant effect, and ROA has a non-significant negative influence on index stock returns.